Administração orofaríngea de colostro e prevenção de infecções em recém-nascidos pré-termo de muito baixo peso ao nascer: ensaio clínico randomizado - Ferreira, Daniela Marques de Lima Mota (2016)
Objective: The purpose of this study was to evaluate the effects of oropharyngeal colostrum administration in very low birth weight (VLBW) preterm infants in first days of life, specially in reduction of late onset sepsis. Study Design: We conducted a double-blind, randomized, placebo-controlled trial and assigned 145 VLBW infants to receive 0.2 mL of colostrum (Colostrum Group) or sterile water (Placebo Group) via oropharyngeal route every 2 hours for 48 hours, beginning in the first 48-72 hours of life. If the infant was assigned to experimental group but, for any reason, colostrum was not available, this infant received oropharyngeal administration of donor human milk (DHM Group). Immunoglobulin A (IgA) was measured in serum and urine pre and pos treatment. Clinical data during hospitalization were collected. Results: We found no statistically significant differences in the incidence of late onset sepsis comparing the 3 groups. There were either no differences considering length of hospital stay and mortality. The measurement of IgA in serum and urine were similar pre and pos treatment in the 3 groups. All groups of neonates initiated enteral nutrition with a median of 3 days and were exclusively fed breast milk until a volume of at least 100 mL/Kg/day. Conclusion: We observed no effect of oropharyngeal administration of colostrum in the incidence of late onset sepsis and in levels of IgA in serum and urine before and after protocol treatment. This finding can be justified by the practice of feeding VLBW infants exclusively with breast milk in the first days of life and reinforces the prior knowledge of the importance of early nutrition, especially, with human milk.